2002
DOI: 10.12930/0271-9517-22.2.39
|View full text |Cite
|
Sign up to set email alerts
|

First-Year Student Perceptions of Academic Advisement: A Qualitative Study and Reality Check

Abstract: Researchers on student preferences for academic advising style suggest that students prefer developmental advising but experience prescriptive advising. However, data regarding first-year students are absent from these studies, thus limiting the conclusions. Therefore, I describe first-year students and their expectations and experiences with academic advisement. Students in the study preferred prescriptive advising and described their advising experience as primarily prescriptive. Further examination of first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 28 publications
4
45
0
2
Order By: Relevance
“…This finding is echoed in Smith's (2002) research, which supports the assertion that college students believe their college advisors take responsibility for functions similar to those of high school guidance counselors, such as knowing the easiest classes, structure and content of each course, and instruction style of the professor. Connecting our model to Smith's findings, we argue that expectations of university advising proceed from experiences with high school guidance counselors and also explain the way student interpretations of advisor accessibility, communication, and relational qualities are colored by the process experienced during their transition.…”
Section: The Model Of Student Perception Developmentsupporting
confidence: 54%
See 2 more Smart Citations
“…This finding is echoed in Smith's (2002) research, which supports the assertion that college students believe their college advisors take responsibility for functions similar to those of high school guidance counselors, such as knowing the easiest classes, structure and content of each course, and instruction style of the professor. Connecting our model to Smith's findings, we argue that expectations of university advising proceed from experiences with high school guidance counselors and also explain the way student interpretations of advisor accessibility, communication, and relational qualities are colored by the process experienced during their transition.…”
Section: The Model Of Student Perception Developmentsupporting
confidence: 54%
“…We found that the transition from meeting with high school guidance counselors to working with college academic advisors challenges students (F ¼ 154, 17%) because the distinction between the two professions remains unclear (Smith, 2002). Some students explained that their interactions with high school guidance counselors involved more than scheduling, checking grades, and preparing for college.…”
Section: Difficulty Making the Distinction Between Counselors And Advmentioning
confidence: 94%
See 1 more Smart Citation
“…Students who perceive academic advisors as good or excellent are more likely to interact with faculty and perceive the collegiate environment to be more supportive (Creamer & Scott, 2000;Crockett, 1978;Frost, 1991;Gordon & Habley, 2000;Habley, 2000;Ishler, 2005;McArthur, 2005;Smith, 2002;Wychoff, 1999). Academic advising plays an integral role in students' success throughout their educational career.…”
Section: Campus Resources and Counseling Servicesmentioning
confidence: 99%
“…Some concluded that university students prefer the prescriptive approach (Fielstein, 1989;Motterella, Fritzsche, & Cerabino, 2004;Smith, 2002); others found that students prefer the developmental approach (Broadbridge, 1996;Herndon, Kaiser, & Creamer, 1996;Winston & Sandor, 1984). Because findings show no consistent preference on the approach, conclusions about the most appropriate or effective in meeting students' needs remain elusive.…”
Section: Students' Preferences For Academic Advising Approachmentioning
confidence: 99%